Humoral Immune Responses of Dengue Fever Patients Using Epitope-Specific Serotype-2 Virus-Like Particle Antigens - Crill, Wayne D.; Hughes, Holly R.; Delorey, Mark J.; Chang, Gwong-Jen J. (PloS one, 2009)
Dengue virus (DENV) is a serious mosquito-borne pathogen causing significant global disease burden, either as classic dengue fever (DF) or in its most severe manifestation dengue hemorrhagic fever (DHF). Nearly half of the world's population is at risk of dengue disease and there are estimated to be millions of infections annually; a situation which will continue to worsen with increasing expansion of the mosquito vectors and epidemic DF/DHF. Currently there are no available licensed vaccines or antivirals for dengue, although significant effort has been directed toward the development of safe and efficacious dengue vaccines for over 30 years. Promising vaccine candidates are in development and testing phases, but a better understanding of immune responses to DENV infection and vaccination is needed. Humoral immune responses to DENV infection are complex and may exacerbate pathogenicity, yet are essential for immune protection. In this report, we develop DENV-2 envelope (E) protein epitope-specific antigens and measure immunoglobulin responses to three distinct epitopes in DENV-2 infected human serum samples. Immunoglobulin responses to DENV-2 infection exhibited significant levels of individual variation. Antibody populations targeting broadly cross-reactive epitopes centered on the fusion peptide in structural domain II were large, highly variable, and greater in primary than in secondary DENV-2 infected sera. E protein domain III cross-reactive immunoglobulin populations were similarly variable and much larger in IgM than in IgG. DENV-2 specific domain III IgG formed a very small proportion of the antibody response yet was significantly correlated with DENV-2 neutralization, suggesting that the highly protective IgG recognizing this epitope in murine studies plays a role in humans as well. This report begins to tease apart complex humoral immune responses to DENV infection and is thus important for improving our understanding of dengue disease and immunological correlates of protection, relevant to DENV vaccine development and testing.